The metaphysics of historical Jesus research: a Prolegomenon to a future quest for the historical Jesus - Rowlands, Jonathan (Routledge, Taylor & Francis Group, 2023)
Cover -- Endorsement Page -- Half Title -- Title Page -- Copyright Page -- Dedication -- Table of Contents -- Preface -- List of Abbreviations -- Part I Worldviews and Historiographical Decision-Making -- Chapter 1 Theology and History, Then and Now -- Chapter 2 Defining Metaphysics -- Chapter 3 The Concept of a Worldview -- Chapter 4 Worldviews and Historiographical Decision-Making -- Chapter 5 Characterising Secular Scholarship -- Part II Worldviews and Historical Jesus Research -- Chapter 6 Metaphysics and the First 'Quest' -- Chapter 7 Metaphysics and the Second 'Quest' -- Chapter 8 Metaphysics and the Third 'Quest' -- Chapter 9 Metaphysics and N.T. Wright -- Chapter 10 Expanding the Boundaries of Historical Jesus Research -- Bibliography -- Author Index -- Subject Index.